Phenotypic Characterization of Coagulase-Negative Staphylococcus Strains Isolated from a High Risk Neonatal Unit - Elsa Velazco; Beatriz Nieves; Evelyn Alviarez; Maria Araque; Elsa Salazar; Betty Gutierrez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2008)
Nosocomial infections constitute a public health problem due to a high level of morbidity and mortality, generating high health-care costs in hospitals. Intensive care units are the principal areas where a high incidence of nosocomial infections is reported. Bacterimia is the principal infection involving a large variety of microorganisms; coagulase-negative Staphylococcus (CNS) is one of the most frequently isolated pathogens. Therefore, the purpose of this study was to characterize the 32 strains of CNS isolated from neonates with nosocomial infections in the High Risk Neonatal Unit (HRNU) at the University of the Andes Hospital Autonomous Institute (UAHAI), Mérida, Venezuela, from December 1997 to April 1999. Results showed that the isolation of CNS was 47.37%; 78.1% of the species were isolated from neonates with bacteremia. S. epidermidis (46.9%), and S. warneri (34.4%) were the species most frequently found. All pathogens showed resistance to penicillin and 18.8% of them produced -lactamase; 68.8% were resistant to oxacillin and 78.1% to gentamicin. Most of the oxacillin-resistant strains showed MIC values above 0.5 mg/mL and the presence of PBP2a was detected. None of the strains were hyper-producers of -lactamase. Vancomicin and quinuprintin/dalfopristin showed excellent activity against these CNS. Due to the role of CNS as a pathogen in the HRNU of UAHAI, strong asepsis measures during diagnosis and therapeutic invasive procedures must be taken to prevent infections caused by this group of microorganisms.